PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DIINTEGRASIKAN DENGAN MEDIA FLASH CARD DAN QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Priyatno, Novianto Agung; Aimah, Siti; Dwiyamtini, Margaretha Rulik (Journal of Lesson Study in Teacher Education, 2024)
English is a subject which for some students is a difficult subject. There are several factors that cause this, whether from students, teachers or the learning environment. This condition must be addressed immediately so as not to disrupt student learning outcomes. In facing challenges to problems in learning in this class, the author applies a model Problem Based Learning by applying learning media from wordwall and quiziz to increase student learning motivation. This research is a qualitative descriptive study. The impact of action on the implementation of learning steps was obtained from the results of a student survey carried out at the end of the lesson, showing that the learning that had been carried out felt enjoyable. By implementing innovative and fun learning, it encourages students to be active and creative, able to convey their thoughts and ideas both individually and in groups to achieve the expected learning goals